Kepelbagaian dan Kesatuan Dalam Konteks Fiqh al-Ta'ayush di Malaysia Menurut Perspektif Pemikiran Islam: Diversity and Unity in Fiqh al-Ta'ayush Context in Malaysia According to Islamic Perspectives - Mohd Khambali @ Hambali, Khadijah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Diversity is sunnatullah as reflected in surah al-Hujurat 49, verse 13. However, diversity also triggers different ideologies that cause problems especially in relation to the religious community. As such, diversity and unity is one of the point of questions that requires particular attention in the context of Malaysia’s own diverse ethnicity and racial beliefs community. The question of diversity and unity is not a straight forward matter as it relates to all aspects of life as a medium in the relationship of religious community in the context of fiqh al-ta‘ayush (co-existence). There are many issues that affects the Muslims and non-Muslims inferior feelings. This paper emphasized on the concept of diversity in the context of ta‘amul (interaction) that bases on ta‘aruf (knowing each other), tasamuh (tolerance) ta‘awun (helping each other), takaful (sacrifice) and mahabbah (loving and caring); which are based on fiqh al-ta‘ayush. In conclusion, this writing found that diversity embodied the relationship of religious community towards unity and better understanding of the religious philosophical aspect to build al-ta‘ayush among adherents and thus create a harmonic religious life.